Infused water (strawberry and honey) to mothers with emesis gravidarum - Raihanah Fathindya Pratiwi; Suparmi, Suparmi; Widiastuti, Dhias (Jurnal Kesehatan Ibu dan Anak, 2024)
Emesis gravidarum, a common complication during early pregnancy, often leads to discomfort and nutritional deficiencies. Pharmacological treatments are available but may carry side effects and high costs. Therefore, non-pharmacological interventions utilizing natural ingredients such as fruits and honey are gaining interest due to their nutritional benefits and safety profile. This study aimed to examine the effect of infused water containing strawberry and honey on the severity of emesis gravidarum in first-trimester pregnant women. A pre-experimental one-group pretest-posttest design was conducted involving 32 pregnant women in their first trimester at the Toroh 1 Public Health Center, Grobogan, Indonesia. Participants consumed strawberry and honey-infused water daily for four consecutive days. The severity of emesis gravidarum was measured using a visual analog scale (VAS). Data were analyzed using the Wilcoxon signed-rank test, following a normality check with the Shapiro–Wilk test. The average emesis score significantly decreased from 4.81 (SD = 0.738) before the intervention to 2.78 (SD = 0.706) after the intervention. The Wilcoxon signed-rank test revealed a statistically significant difference (Z = -4.930; p < 0.001), indicating that the infused water intervention effectively reduced the severity of emesis gravidarum. Strawberry and honey-infused water significantly reduced symptoms of emesis gravidarum among first-trimester pregnant women. The intervention offers a safe, natural, and cost-effective alternative to pharmacological therapy. These findings support the integration of natural dietary interventions into antenatal care programs as a complementary strategy for managing early pregnancy discomfort.